Philippine bureaucratic capacity for effective governance and development - Aguja, Hilton J. (2006)
The economic success stories of the high performing Asian economies (HPAES) show that economic growth and development is anchored on the capacity of the State to steer the economy along politically-defined priorities. That growth requires a strong state with its concomitant bureaucratic capacity for planning and policy implementation is the lesson to be learned in these experiences.

The broad contours of the Philippines as a state were defined primarily by its colonial experiences. The attendant bureaucracy in the formation of the state and the concomitant outlook towards public service that was to emerge from it was heavily molded by the concrete colonial practices that in general were extractive and exploitative in character.

Given the historical circumstances under which the Philippine state emerged, the resultant state apparatus and its bureaucratic machinery are highly penetrated and overwhelmed by particularistic dictates of powerful political patrons. It has never acquired the wherewithal to assume a developmental role so evident in other Southeast Asian countries.
Keywords: Bureaucracy -- Philippines; Governance -- Philippines